Hydrocarbons – water phase equilibria using the CPA equation of state with a group contribution method. (18th December 2014) - Hajiw, Martha; Chapoy, Antonin; Coquelet, Christophe
Abstract It is proposed in this paper to extend the original group contribution method PPR78 to systems containing water, by combining it to the Cubic–Plus–Association (CPA) equation of state (EoS). Applying simple geometric combination rules, the binary interaction parameter kij(T) can be calculated from interaction parameters between hydrocarbon groups and water. This model, called the GC–PR–CPA is applied to predict hydrocarbons – water mutual solubilities over a wide temperature and pressure range, depending on available literature data. Group interaction parameters, here CH4, C2H6, CH3, CH2, CH, C, CHaro, CH2, cyclic, CHcyclic/Ccyclic, C2H4, CH2, alkene/CHalkene with H2O have been defined with solubility data. Predictions of the developed model have been validated against independent solubility data as well as water content in hydrocarbon rich phase. Predictions of the new model are in good agreement for light and medium hydrocarbons; however, some deviations are observed for heavier hydrocarbons.